Issues and Essence of Distribution Law in Germany: A Contribution in Honour of Professor Charl Hugo - Martinek, Michael (Potchefstroom Electronic Law Journal, 2022)
The focus of this article is on the law of contractual distribution systems which has evolved from the law of sales agents, mainly by way of judicial interpretation and intervention. The article explores the realm of distribution law – mainly – from a German perspective. The law of distribution relates to the contractual, commercial, and competition law aspects concerning the distribution of goods and services. The area comprises forms of indirect distribution through contractual distribution systems by means inter alia of commercial sales agents, licensed distributors and franchisees. However, direct distribution (such as e-commerce through internet sales) plays an important role too and thus requires the consideration of consumer protection law issues. Subject matters of distribution law of wider interest, for example vertical integration systems and the regulatory task of distribution competition and distribution contract law, will be explored. Subsequently, the article highlights current challenges in the field of distribution law, among them the digitalisation and internationalisation of distribution activities.